Elevated fecal levels of the inflammatory biomarker calprotectin in early systemic sclerosis - Hamberg, Viggo; Wallman, Johan K.; Mogard, Elisabeth; Lindqvist, Elisabet; Olofsson, Tor; Andréasson, Kristofer (Rheumatology international, 2023)
Knowledge on gastrointestinal manifestations in early systemic sclerosis (SSc) is limited. We have investigated gastrointestinal inflammation in SSc at the time of diagnosis using the inflammatory biomarker Fecal calprotectin (F-cal). Consecutive patients with suspected SSc were characterized in relation to the 2013 classification criteria for SSc and classified as SSc or SSc-like disease. F-cal levels were measured with a polyclonal ELISA (Calpro A/S, Lysaker, Norway) and levels above 50 µg/g were considered elevated. F-cal levels were compared to those of control subjects without rheumatic disease. Of 137 patients with suspected SSc, 92 were classified as SSc and 45 as SSc-like disease. Median (interquartile range) disease duration among the SSc participants was 2.5 (1.2, 4.6) years. A substantial proportion of participants classified as SSc (35/92, 38%) and SSc-like disease (14/45, 31%) exhibited elevated F-cal compared to the control group (3/41, 7.3%; p < 0.001 and p = 0.007, respectively). Elevated F-cal was associated with proton pump inhibitor usage (OR 7.14; 95% CI 2.56–29.93; p < 0.001). We conclude that elevated F-cal is present in a subgroup of patients with SSc at the time of diagnosis, suggesting that that GI inflammation may be present in this patient group early in the disease course. F-cal did not exhibit potential to differentiate SSc from SSc-like disease.